Case report: Neuropathic pain versus undesirable behavior in a Dachshund after hemilaminectomy surgery for an intervertebral disc extrusion - Santifort, Koen M.; Plonek, Marta; Mandigers, Paul J. J. (Frontiers in Veterinary Science, 2023)
A 5.5-year-old male Dachshund was presented for evaluation because of undesirable behavior including barking, biting, sucking and licking the right-side flank, ventrally and slightly caudally to the level of the surgical incision 7 days after hemilaminectomy for a right-sided L1-2 intervertebral disc extrusion. The dog was being treated with oral gabapentin 10 mg/kg q8h. Repeat clinical examination on three occasions after post-operative discharge did not reveal any signs of hyperesthesia or neurological deficits and the behavior was not observed in the clinic during consultations. During a separate day of hospital admittance with the aim of evaluating for the presence or absence of the behavior, the dog also did not exhibit the behavior. Oral paracetamol 12 mg/kg q8h was added to medical treatment. When the dog was discharged and returned home, the behavior was immediately seen again. When the owners implemented verbal punishment, the behavior immediately ceased. The owner verbally corrected the dogs' behavior for two excitative days. Upon telephone consultation three days later, the owner reported that they only had observed three recurrences of the behavior that immediately ceased following verbal correction and did not recur thereafter. Oral analgesic medication was tapered and discontinued. No recurrence of the behavior was noticed during the next 2 months. The authors postulated the dog possibly expressed signs of neuropathic pain in the post-operative period, or that the behavior was of a 'compulsive disorder-like' nature as it only occurred when the dog was at home and in the presence of the owner. The eventual outcome and result of verbal corrections implemented by the owner seem to support the latter. In conclusion, compulsive-like undesirable behavior should be considered a differential diagnosis in dogs in the post-operative period of procedures possibly associated with the development or expression of signs of neuropathic pain.